A heuristic control framework for heavy‐duty hexapod robot over complex terrain. Issue 4 (21st September 2022) - Hou, Jinmian; Chai, Hui; Li, Yibin; Xin, Yaxian; Chen, Wei
Abstract: The large and heavy‐duty hexapod robot has strong motion stability and load capacity, which promises to have a wide range of application prospects in rescue and disaster relief. Multi‐mode gait and static stability during walking make the hexapod robot adapt to more diverse terrains, while little research has been conducted on the motion control methods of heavy‐duty hexapod robots in complex environments. A novel heuristic whole‐body motion control framework for the heavy‐duty hexapod robot to traverse complex terrain is presented. By splitting the legged locomotion into a single task, the whole‐body motion could be planned in a reasonable time. The terrain adaptation strategy is designed to improve the complex terrain passability. Ground reaction forces are then optimised based on single rigid‐body dynamics with heuristics. This framework utilised simple but powerful heuristics to approximate complex dynamics and allows for a single set of parameters for all task conditions. Simulation results demonstrate the robustness and adaptability of the proposed framework.